Modulating Surface Chemistry of Al Powders for Elastomeric Composites with Applications in Electronic Cooling. Issue 10 (2nd March 2023) - Ma, Qiangqiang; Zhang, Chenxu; Ren, Linlin; Zeng, Xiaoliang; Xu, Jian‐Bin; Sun, Rong; Yao, Yimin
Abstract: Elastomeric composites are an important class of thermal interface materials as they are shape‐adaptive, which can fit uneven interfaces and achieve ideal interfacial heat transfer in electronic cooling. There is often a trade‐off between mechanical and thermal performances in highly filled composites. Here, the surface chemistry of Al powders via introducing dodecyltrimethoxysilane (DTS) upon different grafting densities is precisely controlled. The results show that the DTS grafting density of 0.24 molecule nm −2 endows the composites with optimized mechanical properties. The tensile stress, elongation at break, and Young's modulus are enhanced by 180%, 56%, and 94.4% after DTS grafting, respectively. Meanwhile, the composite possesses a high fracture energy of 356.2 J m −2 with an enhanced strain energy density of 37.6 kPa. The DTS grafting on Al also contributes to higher thermal conductivity (4.4 W mK −1 ) and lower contact thermal resistance (0.52 °C cm 2 W −1 ) of the composites and significantly improves the stability of the composites upon high‐temperature storage. Guidance is provided here on methods and data references for optimizing the performance of elastomeric composites, which helps to expand their practical application in electronic cooling. Abstract : The simultaneous improvement of the overall performance of the elastomeric composites is achieved by the precise regulation of the surface chemistry of Al powders. The appropriate modification of the interfacial layer imparts satisfactory mechanical and thermal performances, along with good stability to the composites, which perform well in electronic cooling.